1987
DOI: 10.1093/cvr/21.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Beta adrenergic blockade with propranolol and atenolol in the exercising dog: evidence for beta2 adrenoceptors in the sinoatrial node

Abstract: To test the hypothesis that beta 2 adrenergic receptors mediate the chronotropic more than the inotropic response to endogenous catecholamines the effects on the haemodynamic responses to exercise in dogs of the beta 1 specific antagonist atenolol were compared with those of the non-selective beta antagonist propranolol. Heart rate, left ventricular dP/dt at 40 mmHg developed pressure (dP/dt40), and oxygen consumption (VO2) were determined at seven to eight exercise levels in 16 chronically instrumented adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…However, it does not mean such stimulation of the re ceptors to be physiological relevant (24). The effects of atenolol and propranolol were studied on the hemody namic responses induced by exercise in dogs and sug gested that ,82-adrenoceptors in the SA node might be stimulated by circulating catecholamines and contri buted greatly to sympathetic modulation of HR during heavy exercise in dogs (6). It was shown that failing hu man ventricular myocardium contained a relative high proportion of X82-adrenoceptors, due to selective down regulation of ,81-adrenoceptors using a radioligand binding study (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it does not mean such stimulation of the re ceptors to be physiological relevant (24). The effects of atenolol and propranolol were studied on the hemody namic responses induced by exercise in dogs and sug gested that ,82-adrenoceptors in the SA node might be stimulated by circulating catecholamines and contri buted greatly to sympathetic modulation of HR during heavy exercise in dogs (6). It was shown that failing hu man ventricular myocardium contained a relative high proportion of X82-adrenoceptors, due to selective down regulation of ,81-adrenoceptors using a radioligand binding study (25).…”
Section: Discussionmentioning
confidence: 99%
“…NE is pos tulated as a selective 8 1-adrenoceptor agonist to / adrenoceptors (2 5), although it has been suggested that circulating catecholamines cause a positive chrono tropic effect mediated by ,E2-adrenoceptors in the ex ercising dog (6).…”
mentioning
confidence: 99%
“…5). Although Lands et al (32,33) first subclassified beta adrenoceptors into beta-1 and beta-2 sub types with absolute organ-specific distribu tion such as beta-1 receptors in the heart and beta-2 receptors in the lung, it has been sug gested that both receptor subtypes exert a physiological role in the cat, dog and human hearts from pharmacological (20,34,35), biochemical (30,36,37) and receptor-bind ing studies (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the reduction in peak heart rate response by non-selective ,B-adrenoceptor blockers may be due to blockade of the 12-as well as 13l-adrenoceptors (Friedman et al, 1987). This may be a limitation in the use of exercise induced tachycardia for comparison of equipotent doses of 13-adrenoceptor antagonists with respect to 13l-mediated responses.…”
Section: Heart Ratementioning
confidence: 99%
“…Both ,B-selective and non-selective 3-adrenoceptor antagonists augment adrenaline levels during exercise (Gullestad et al, 1989b;Irving et al, 1971), and this may stimulate 132-adrenoceptors in the myocardium directly at maximal exercise. Accordingly, the reduction in peak heart rate response by non-selective ,B-adrenoceptor blockers may be due to blockade of the 12as well as 13l-adrenoceptors (Friedman et al, 1987). This may be a limitation in the use of exercise induced tachycardia for comparison of equipotent doses of 13-adrenoceptor antagonists with respect to 13l-mediated responses.…”
Section: Heart Ratementioning
confidence: 99%